Arabic Problem-Based Learning for Religious Moderation: ‎Classroom Action Research in Islamic Education - Erlina Erlina; Umi Hijriyah; Fachrul Ghazi; Sulthan Syahril; Muhammad Sufian (Yayasan Darussalam Bengkulu, 2025)
This study aimed to evaluate the effectiveness of integrating religious moderation values into Arabic language instruction through a Problem-Based Learning (PBL) model refined by Classroom Action Research (CAR). The objective was to enhance students’ linguistic competence while fostering moderate dispositions such as tolerance, balance, and non-violence. The study applied a two-cycle CAR design (planning–action–observation–reflection) involving one undergraduate class of Islamic Religious Education. Learning materials and PBL cases were developed around themes of tawassuṭ (moderation), justice, and equity, and implemented through case analysis, group discussion, and role-play. Data were gathered from performance assessments, observation checklists, field notes, and attitude questionnaires, analyzed using descriptive statistics and thematic reduction across cycles. Findings indicated consistent improvements from Cycle 1 to Cycle 2 in student engagement, reading comprehension, translation accuracy, and the demonstration of balanced reasoning and respectful disagreement in Arabic discourse. These gains were supported by iterative refinements in task design, scaffolded questioning, and structured peer feedback. Conclusion: The study concludes that moderation-oriented PBL, developed through iterative CAR cycles, provides a practical and replicable approach to simultaneously strengthening Arabic language proficiency and internalizing moderation values within Islamic higher education.